Extensive Cryptic Diversity Within the Physalaemus cuvieri - Physalaemus ephippifer Species Complex (Amphibia, Anura) Revealed by Cytogenetic, Mitochondrial, and Genomic Markers - Nascimento, Juliana (2019)
Previous cytogenetic and phylogenetic analyses showed a high variability in the frog taxa Physalaemus cuvieri and Physalaemus ephippifer and suggested the presence of undescribed diversity in this species complex. Here, by 1) adding specimens from the Brazilian Amazon region, 2) employing sequence-based species delimitation approaches, and 3) including RADseq-style markers, we demonstrate that the diversity in the P. cuvieri–P. ephippifer species complex is even greater than previously suspected. Specimens from Viruá and Western Pará, located at the Guiana Amazonian area of endemism, were recovered as distinct from all previously identified lineages by the phylogenetic analyses based on mitochondrial DNA and RAD markers, a PCA from RAD data, and cytogenetic analysis. The sequence-based species delimitation analyses supported the recognition of one or two undescribed species among these Amazonian specimens and also supported the recognition of at least three other species in the P. cuvieri–P. ephippifer species complex. These new results reinforce the need for a comprehensive taxonomic revision.